Additive Manufacturing and Performance of Architectured Cement‐Based Materials. Issue 43 (29th August 2018) - Moini, Mohamadreza; Olek, Jan; Youngblood, Jeffrey P.; Magee, Bryan; Zavattieri, Pablo D.
Abstract: There is an increasing interest in hierarchical design and additive manufacturing (AM) of cement‐based materials. However, the brittle behavior of these materials and the presence of interfaces from the AM process currently present a major challenge. Contrary to the commonly adopted approach in AM of cement‐based materials to eliminate the interfaces in 3D‐printed hardened cement paste (hcp) elements, this work focuses on harnessing the heterogeneous interfaces by employing novel architectures (based on bioinspired Bouligand structures). These architectures are found to generate unique damage mechanisms, which allow inherently brittle hcp materials to attain flaw‐tolerant properties and novel performance characteristics. It is hypothesized that combining heterogeneous interfaces with carefully designed architectures promotes such damage mechanisms as, among others, interfacial microcracking and crack twisting. This, in turn, leads to damage delocalization in brittle 3D‐printed architectured hcp and therefore results in quasi‐brittle behavior, enhanced fracture and damage tolerance, and unique load‐displacement response, all without sacrificing strength. It is further found that in addition to delocalization of the cracks, the Bouligand architectures can also enhance work of failure and inelastic deflection of the architectured hcp elements by over 50% when compared to traditionally cast elements from the same materials. Abstract : 3D‐printed architectured cement‐based materials exhibit improved mechanical properties compared with their cast counterparts. The presence of heterogeneous interfaces, combined with control of the architecture, promotes unique damage mechanisms, such as interfacial cracking and crack twisting, that lead to damage delocalization. This delocalization can be energetically favorable, thus resulting in more efficient energy dissipation, promotion of toughening, increase in damage tolerance, quasi‐brittle behavior, unique load‐displacement response, and flaw‐tolerant properties; all without sacrificing the strength.